Puzzle-Based Pop-Up Media Book on Science Subject in Elementary School - Aprilia Agata; I Made Tegeh; Gusti Ayu Putu Sukma Trisna (International Journal of Elementary Education, 2022)
Teachers in teaching use one-way lectures and question and answer, causing students to tend to be passive. It is because students only listen to the teacher's explanation, take notes, and then work on the questions. It can lead to boredom which results in reduced student activity during learning. This study aims to develop a puzzle-based pop-up book media on the content of science learning in elementary schools. This type of research is developed using the ADDIE research model. The pop-up book media developed was assessed by 2 material experts, 2 media experts, 1 teacher as a practitioner response, and 10 students as student responses. The methods used to collect data are observation, interviews, and questionnaires. The instrument used in collecting data is a questionnaire. The technique used to analyze the information is descriptive qualitative and quantitative analysis. This study obtained results from material experts, a whole of 91% (very good). The assessment from media experts is 87.5% (very good). The practitioner's response test results are 96% (very good). The overall student response test results were 95.6% (very good). It is concluded that the pop-up book media on the material of my nation's cultural diversity in grade IV Elementary School is appropriate to use.